Optimising sample preparation to enhance contrast-to-noise ratio in X-ray phase contrast tomography white matter (WM) imaging of the central nervous system - Fratini, Michela; Massimi, Lorenzo; Brun, Francesco; Batey, Darren; Bukreeva, Inna; Mittone, Alberto; Bravin, Alberto; Longo, Elena; Tromba, Giuliana; Giove, Federico; Cipiccia, Silvia; Sierra, Alejandra (Frontiers in Physics, 2025)
The choice of fixative is critical in X-ray phase-contrast tomography (XPCT) because it affects tissue preservation, contrast enhancement and compatibility with other imaging techniques. A careful selection and optimization of fixatives can lead to significant improvements in the quality and accuracy of imaging results, which is especially important when studying complex biological systems such as those involved in neurodegeneration, where it is crucial to maintain the fine details of the Grey Matter (GM) and White Matter (WM) structures. Dehydration with ethanol and xylene is commonly used as it effectively removes water while minimising structural alterations. Using perfusion in ethanol and dehydration in xylene as a secondary fixative can increase the contrast, thereby improving the visibility of myelinated fibers without using a contrast agent. In this paper we discuss an optimised fixation method to significantly enhance the contrast and boost the signal to noise ratio (SNR) in XPCT images of WM in the central nervous system (CNS).